Quality evaluation of stallion frozen semen supplemented with cysteine and ascorbic acid - Alamaary, Mohammed Saad M (2019)
Semen cryopreservation offers numerous advantages for the livestock animal industry and new reproduction technologies. This technique increases the overall pregnancy rate and improves genetics. In horses, the conception rate using this technique remains lower, compared to using fresh semen. Stallion spermatozoa revealed high sensitivity to freezing and thawing procedures. During cryopreservation procedures, stallion spermatozoa are subjected to damage, primarily due to osmotic and oxidative stress that influence the sperm structure and functionality. Therefore, this study aimed to improve the cryopreserved semen quality and fertility prediction of cryopreserved semen in Arabian stallions. The primary objective of the current study was to determine the impact of adding antioxidants (cysteine and ascorbic acid) to the freezing extender, and investigating their capacity to counteract the reactive oxygen species ROS during freezing and thawing procedures. Seven Arabian stallions were used for the semen collection, using either the Missouri model of artificial vagina, or the automated semen phantom collection (Equidame® phantom Haico-Finland). The gel was removed using a gauze filter from all samples, which were initially evaluated for volume, sperm concentration and motility. Only semen samples with at least 200×106 sperm/ml and motility > 60 % were used in these experiments. The selected ejaculation was diluted (1:1) by a centrifuge media and divided into the number of samples required, then centrifuged at 800g for 10 minutes to remove the seminal plasma. The supernatant was discarded, and the pellet was resuspended with the semen freezing extender. The extended samples were cooled to 4 °C for 90 minutes, before being packaged in 0.5 mL straws. The samples were then frozen using either the styrofoam box with liquid nitrogen vapor technology, or a programmable freezer (Automatic Freezer with Windows®-tablet, 230 V, Minitube, Germany) (60°C/min. to–140 °C). After one week, the straws were thawed in a water bath at 37ºC for 30 seconds, and evaluated for general motility, progressive motility, VSL, VCL, VAP, LIN, STR, sperm concentration, normal and abnormal sperm morphology, sperm membrane integrity, viability, acrosome integrity and oxidative stress. The post-thawed semen was analyzed for glutamic oxaloacetic transaminase (GOT), glutamic-pyruvate (GPT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), and γ-glutamyl transpeptidase (GGT) enzymes, to determine their efficiency in the fertility prediction for post-thawed semen. A total of fifty mares were used for artificial insemination. The estrus mares with a follicle of ≥35 mm in diameter were injected with 3000 IU of human chorionic gonadotrophin (hCG), and inseminated using one dose after ovulation. Each dose contains 800×106 of total sperm. Flexible 75 cm pipettes (Minitube) were used to deposit the post-thawed semen dose in the uterine horn. The effect of using four extenders in the quality of frozen semen in Arabian stallions was examined to determine the performance of frozen extenders prepared in the laboratory, compared to the commercial extenders. HF-20 and Tris-based extenders were prepared locally and cryopreserved in the same environment with the commercial extenders (INRA Freeze® IMV Technologies France, and EquiPlus Freeze® Minitube Germany). Cryopreserved samples from all extenders were evaluated in vitro, and were used for artificial insemination (AI). In the current study, the application of HF-20 extender revealed acceptable frozen semen quality, while Tris-based extender revealed poor post-thawed semen, compared to the commercial extenders. The effect of adding cysteine and ascorbic acid at concentrations of 0, 0.25, 0.5, 1, 2 and 4 mg/ml on the quality of frozen semen in Arabian stallions were also evaluated through assessing the oxidative stress, motility pattern, sperm membrane integrity, viability and acrosome integrity. Subsequently, the best concentration of cysteine and ascorbic acid were used for AI to evaluate the effect of these antioxidants on the spermatozoa fertility. The supplementation of cysteine and ascorbic acid were shown to raise the oxidative stress (OS) on post-thawed semen samples, compared to the control. The increase of OS affected negatively the sperm motility, sperm membrane integrity and viability, especially with a high concentration of cysteine and ascorbic acid added. However, the addition of cysteine and ascorbic acid showed better sperm morphology and acrosome integrity. The ascorbic acid in this study exhibited poor post-thawed semen fertility, whereas cysteine exhibited a pregnancy rate that was in the same range with the control group. The effect of cysteine and ascorbic acid on GOT, GPT, ALP, LDH, and GGT enzymes concentration on the cryopreserved semen samples were assessed to determine its efficiency as a marker of the post-thawed semen quality. The level of these enzymes was compared to the sperm motility pattern, viability, morphology and sperm membrane integrity. Using ALP, LDH and GGT, enzymes can act as a reliable marker of post-thawed semen quality. The GOT and GPT enzymes could not be used as reliable parameters for frozen semen in horses. Furthermore, the supplementation of cysteine and ascorbic acid to the semen freezing extender exposed a deleterious effect on the ALP, LDH and GGT enzyme level and function on post-thawed stallion’s semen.